Plant growth and development: A molecular approach - Donald E Fosket (Academic, 1994)
The book presents the field of plant development from both molecular and genetic perspectives. This field has elvoved at a rapid rate over the past five years through the increasing exploitation of the remarkable plant Arabidopsis. Each chapter concludes with questions for study and review as well as suggestions for further reading. Illustrated with two-color drawings and graphs throughout, and containing up-to-date and comprehensive coverage, the book will excite and inform students as it increases their understanding of plant science